2021
DOI: 10.1007/s00253-021-11097-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic secretome engineering in Yarrowia lipolytica for consolidated bioprocessing on polysaccharide resources: review on starch, cellulose, xylan, and inulin

Abstract: Consolidated bioprocessing (CBP) featuring concomitant hydrolysis of renewable substrates and microbial conversion into value-added biomolecules is considered to bring substantial benefits to the overall process efficiency. The biggest challenge in developing an economically feasible CBP process is identification of bifunctional biocatalyst merging the ability to utilize the substrate and convert it to value-added product with high efficiency. Yarrowia lipolytica is known for its exceptional performance in hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Consolidated bioprocessing (CBP) requires the simultaneous production of hydrolases able to degrade plant-derived polymeric substrates and of enzymes allowing the microbial conversion of the released sugars into value-added compounds, in a single step. The progresses that have been made in this competitive research area have been reviewed in a very recent publication, in which the authors discuss the economic advantages of CBP, simulate different industrial CBP models based on GM Y. lipolytica and calculate the associated costs [ 319 ]. All these tools and strategies will contribute to establish Y. lipolytica as a workhorse for a wide range of applications in the very competitive world of white biotechnology.…”
Section: A Brave New World Of Engineered Strains: Tools and Strategies For Building Y Lipolytica Cell Factoriesmentioning
confidence: 99%
“…Consolidated bioprocessing (CBP) requires the simultaneous production of hydrolases able to degrade plant-derived polymeric substrates and of enzymes allowing the microbial conversion of the released sugars into value-added compounds, in a single step. The progresses that have been made in this competitive research area have been reviewed in a very recent publication, in which the authors discuss the economic advantages of CBP, simulate different industrial CBP models based on GM Y. lipolytica and calculate the associated costs [ 319 ]. All these tools and strategies will contribute to establish Y. lipolytica as a workhorse for a wide range of applications in the very competitive world of white biotechnology.…”
Section: A Brave New World Of Engineered Strains: Tools and Strategies For Building Y Lipolytica Cell Factoriesmentioning
confidence: 99%
“…Beside their interest for the design of metabolic engineering strategies, GEMs can also be applied to predicting the metabolic responses of yeast cells to environmental conditions such as industrial-scale production, as demonstrated at the University of Graz (Austria) during the optimization of a Y. lipolytica bioprocess for lipid production [276]. Some statistical modeling tools, such as response surface methodology, are also now currently applied to bioprocess optimization, from wild-type as well as for GM strains [277][278][279][280]. As seen above in Section 2.3.3, a lot of research is performed on remodelling the hydrolytic secretome of Y. lipolytica in order to allow the use of plant biomass as a renewable and cheap carbon source, an approach aiming towards sustainable development and circular bio-economy.…”
Section: Adaptative Evolution Strategies and Bioprocess Engineeringmentioning
confidence: 99%
“…Yarrowia lipolytica is a non-conventional yeast with significant biotechnological potential due to its native ability to produce bio-surfactants, γ -decalactone, citric acid, intracellular lipids and lipase [ 94 ]. It has undergone multiple engineering studies to increase its hydrolytic secretome to include growth on complex polysaccharides such as starch, cellulose, xylan and inulin.…”
Section: Consolidated Bioprocessingmentioning
confidence: 99%
“…Genome analysis of Y. lipolytica revealed the presence of multiple intracellular and extracellular β-glucosidase genes and putative cellobiose transporters, which explained why cellobiose could be assimilated intracellularly, but growth on cellulose was not possible [ 95 ]. Growth on pre-treated corn stover was achieved (50%) after engineering in the T. reesei cellulase genes EGII and CBHII [ 94 ]. A dormant pathway for xylose utilisation was found in the Y. lipolytica genome, but not xylan degradation.…”
Section: Consolidated Bioprocessingmentioning
confidence: 99%
See 1 more Smart Citation